Shang-chi by gene luen yang, volume 3 ebook Family of origin. - Yang, Gene (Shang-Chi (2020), 2022)
Collects Shang-Chi (2021) #7-12, Marvel's Voices: Identity (2021) #1 (Shang-Chi story). Prepare to learn the secrets of Shang-Chi's mother! Arrows will fly as the first meeting of Shang-Chi's parents is revealed - and not the Cupid's arrows! Who exactly was the woman who gave birth to the legend? And how could someone so virtuous and heroic possibly fall for an evil warlord like Zheng Zu? All will be revealed! In the present, the tides of fortune begin to turn against Shang-Chi as the mastermind who has been gathering all of his foes steps out of the shadows and stands revealed at last! His objective? To destroy everyone in Shang-Chi's bloodline! Plus: Our hero must face his dark side as he asks himself, ""What If?""